A study of the marine algal epiphyte, Placophora binderi (J. Agardh) J.Agardh (Ceramiales : Rhodophycophyta) - Hartley, Diana Hendy (Rhodes University, Faculty of Science, Botany Department, 1986)
Placophora binderi can be described as an "obligate epiphyte" as it does not respond well to any culture conditions and is found growing only on other algae in the natural environment. This habit may have arisen as a response to the best available substrate in a harsh environment (Harlin 1971; Moss 1982). Any nutrient transfer which may occur between Placophora binderi and its basiphyte, usually various species of Codium, is probably by diffusion as rhizoids do not penetrate the basiphyte cells but simply lie between the Codium utricles providing better anchorage. A triphasic life history exists with isomorphic gametophyte, carposporophyte and tetrasporophyte generations. The male and female gametophytes are dioecious. This study confirms Scagel's (1953) observations for the development of the juvenile, mature and reproductive thallus. The juvenile develops as an erect polysiphonous thallus which produces a prostrate lobe as an adventitious branch from the basal segments. This prostrate lobe develops into the dorsiventrally flattened mature thallus. Reproductive structures are produced on erect branches which are initiated at the mature thallus margins. The gametophyte develops on evanescent trichoblasts produced on erect reproductive branches while the tetra sporophyte develops within these erect branches. The female gametophyte has a four-celled carpogonial branch with an auxiliary cell forming after fertilisation from the supporting cell. At the electron microscope level several vesicle types were seen in the reproductive organs. In the male, spermatial vesicles are produced which probably aid in release of the spermatia (Kugrens 1980). These are also visible under the light microscope. In carposporogenesis and tetrasporogenesis, three vesicle types are produced. Striated vesicles appear for a short while during the early stages and probably function as protein stores. Fibrillar vesicles are large and visible under the light microscope. These probably act as carbohydrate storage organelles (Triemer and Vasconcelos 1979; Kugrens and West 1973c; Tripodi 1971). Cored vesicles appear late in sporogenesis and probably aid in adhesion once the spores have settled (Chamberlain and Evans 1973; Wetherbee 1978). Carpospores follow the "serial release" type pattern observed in Polysiphonia (Boney 1978). Tetraspores are released singly via a rupture in the tetrasporangial wall as in Ceramium rubrum (Chamberlain and Evans 1973). Both carpospores and tetraspores germinate in the typical bi-polar Ceramium-type pattern described by Dixon (1973)
Keywords: Epiphytes; Marine algae; Codium; Ceramiales